Holistic development of human talent – leveraging on e-maarah tuition program through the network of mosque (Nom) - Ahmad Dahlan, Abdul Rahman; Songib, Anis Suraya; Ismail, Rabi'atul Adawiyah; Mohd Mokhtar, Amilia; Moktar@Mokhtar, Nor Shahidah (International Organisation of Scientific Research (IOSR), 2014)
Education is an essential process for every human being especially school children. However, parents are more concern with their children‟s Intelligent Quotient (IQ) achievement, neglecting or less focus on the Emotional Quotient (EQ) and Spiritual Quotient (SQ) achievement. This paper intends to propose a conceptual solution that provides a holistic development of school children focusing on IQ, EQ, and SQ with „ukhrawi‟ (or Hereafter) elements. The paper is based on literature review, real world observations and adopting business model canvas (BMC) framework in building a conceptual solution for holistic development of human talent. This paper explores the opportunity of providing holistic and balanced education to school children by leveraging the network of mosques just like what the Prophet Muhammad‟s PBUH used to do during his time, and at the same time generating sustainable revenue and profit utilizing technology-based solution. The findings of this paper show that cyber world, through the creative use of ICT and Internet, has been widely used around the world by entrepreneurs to build businesses based on sound human values and principles that takes into account the numerous benefits and virtues offered to the people, planet, and profits.